2001
DOI: 10.1007/s004420000551
|View full text |Cite
|
Sign up to set email alerts
|

Epichloë grass endophytes increase herbivore resistance in the woodland grass Brachypodium sylvaticum

Abstract: Endophytic fungi of the genus Epichloë and their asexual Neotyphodium forms are thought to interact mutualistically with their host grasses, providing protection for the host against herbivores and pathogens mediated by fungal alkaloids. Most previous research has concentrated on agronomically important grasses, such as tall fescue, and its interactions with livestock grazers or invertebrate herbivores. In this study we focus on the woodland grass Brachypodium sylvaticum which is infected by the strictly host-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 44 publications
(63 reference statements)
2
52
0
1
Order By: Relevance
“…The outcomes of these studies span the range of negative to neutral to positive effects of endophyte infection. Some studies involving native grasses show reduced herbivory or increased insect deterrence on infected grasses relative to uninfected grasses (Christensen and Latch, 1991, Brem and Leuchtmann, 2001, Gonthier et al, 2008, Clement et al, 1997, Clement et al, 2005, Tintjer and Rudgers, 2006and Afkhami and Rudgers, 2009, whilst other studies showed no difference (Christensen and Latch, 1991, Lopez et al, 1995, Clement et al, 1997, Tintjer and Rudgers, 2006and Afkhami and Rudgers, 2009, depending on herbivore species and endophyte strain. Note that most of these studies used generalist insect pest species, such as the armyworm and bird oat cherry aphid, in bioassay tests.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of these studies span the range of negative to neutral to positive effects of endophyte infection. Some studies involving native grasses show reduced herbivory or increased insect deterrence on infected grasses relative to uninfected grasses (Christensen and Latch, 1991, Brem and Leuchtmann, 2001, Gonthier et al, 2008, Clement et al, 1997, Clement et al, 2005, Tintjer and Rudgers, 2006and Afkhami and Rudgers, 2009, whilst other studies showed no difference (Christensen and Latch, 1991, Lopez et al, 1995, Clement et al, 1997, Tintjer and Rudgers, 2006and Afkhami and Rudgers, 2009, depending on herbivore species and endophyte strain. Note that most of these studies used generalist insect pest species, such as the armyworm and bird oat cherry aphid, in bioassay tests.…”
Section: Introductionmentioning
confidence: 99%
“…Since fly larvae depend on fertilized stroma as food source, both fly and fungus clearly profit from this mutualistic association. The grass host, in turn, benefits from the fungus-produced secondary metabolites that may provide increased resistance to herbivores or pathogens (Shimanuki 1987;Breen 1994;Brem & Leuchtmann 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of incidental codivergence and incongruence may reflect the variable nature of transmission among Epichloë species. Asexual, mutualistic species are associated with vertical transmission, which would promote codivergence; sexual species are associated with pathogenicity and horizontal transmission, traits that may increase the opportunities for successful host switching (Brem and Leuchtmann 2001;Clay and Schardl 2002).…”
Section: Epichloë and Incidental Codivergencementioning
confidence: 99%